Analysis of Using Tik Tok Social Media in an Efforts to Increase Adolescent Girls Knowledge of Anemia Prevention at SMAN 3 Kediri - Laily Nurhanifah; Dwianggimawati, Mayta Sari (Universitas STRADA Indonesia, 2024)
Based on data from the Health Office of the City of Kediri, the risk of anemia in adolescents in the age range of 15-18 years from a total examination of 16,524 adolescents was 457 (2.76%) female adolescents and 19 (0.11%) male adolescents. Tik Tok is a popular media for various groups, including teenagers. Tik tok social media is able to provide interesting education because it uses movement, animation with a short duration. The provision of anemia education is carried out to prevent anemia. This study aims to analyze differences in adolescent knowledge of anemia prevention. Analyzing differences in adolescent knowledge of anemia prevention in the control group and the treatment group. This research uses quantitative methods with Quasi Experimental Design (Pre test – Post test Control Group Design). The research population was all students of class XI SMAN 3 Kediri. A sample of 140 respondents was obtained by proportional random sampling technique into the treatment and control groups. The research instrument is a structured questionnaire. Data analysis using T Independent Test and Paired T Test. There are differences in pre and post test scores in the two groups. The mean value of the treatment pre-test was 14 points and the control group was 11 points. Meanwhile, the mean value of the post-test in the treatment group was 15 points and the control group was 12 points. The results of statistical tests showed that the difference in knowledge before and before providing education with an alpha value of 0.000 <0.05. Educational videos through tik tok can increase respondents' knowledge. There is a difference in knowledge between the control group and the treatment group, it can be concluded thah H0 is accepted. It is hoped that young women can increase their knowledge regarding anemia in various media. For the puskesmas, they can provide counseling to young women who reveal to the school to show educational videos in each class.